Holistic Education in KH. Imam Zarkasyi's Educational Philosophy: Implementation at Pondok Modern Darussalam Gontor - Mardiyah; Melikai Jihan El-Yunusi; Najwa Sajida El Yunusi (Universitas Al-Amien Prenduan, 2026)
Although numerous studies have examined KH. Imam Zarkasyi’s educational philosophy, few have explored it from the perspective of holistic education. Zarkasyi developed an integrative educational model that combines religious values with intellectual advancement while fostering students’ intellectual, spiritual, emotional, and kinesthetic development. The novelty of this study lies in examining PMD Gontor as an institution that systematically implements an integrative curriculum based on holistic educational principles. This study aims to analyze the relevance of holistic education to KH. Imam Zarkasyi’s educational thought. It employs qualitative library research using books, journal articles, personal writings, online sources, and other relevant documents. The findings show that holistic education is systematically implemented in PMD Gontor through educational goals, vision, mission, and institutional values that emphasize the balanced development of human potential. Its autonomous Kulliyatul Mu'allimin al-Islamiyah curriculum integrates religious and general sciences through the Direct Method, deep learning, and project-based learning, enabling students to develop intellectual competence, practical skills, and moral character simultaneously. Teacher quality is strengthened through continuous professional development, while student assessment is conducted periodically to evaluate academic achievement alongside character, mental, and spiritual growth. Holistic education is further reinforced through collaboration among teachers, administrators, students, parents, alumni, and the wider community, creating an integrated educational ecosystem. These findings demonstrate that Zarkasyi’s educational philosophy remains highly relevant as a holistic model of Islamic education that balances intellectual, spiritual, moral, and practical development in preparing students to contribute positively to society.